Proceedings of the 27th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2019
DOI: 10.1145/3347146.3359093
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Predictability Limits in Human Mobility

Abstract: Human mobility has been studied from different perspectives. One approach addresses predictability, deriving theoretical limits on the accuracy that any prediction model can achieve in a given dataset. This approach focuses on the inherent nature and fundamental patterns of human behavior captured in the dataset, filtering out factors that depend on the specificities of the prediction method adopted. In this paper, we revisit the state-of-the-art method for estimating the predictability of a person's mobility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Regardless of the applied methods (e.g., Markov chains, Naive Bayes, neural networks), the type of prediction (i.e., next-cell or next place) or the used data sets (e.g., GPS, CDR, surveys), the accuracy of prediction never reaches the coveted 100%. The reasons are manyfold: the lack of ground truth data, human beings' complex nature and behavior, and the difficulty to forecast visits to non-routinary areas and discoveries of new places [8].…”
mentioning
confidence: 99%
“…Regardless of the applied methods (e.g., Markov chains, Naive Bayes, neural networks), the type of prediction (i.e., next-cell or next place) or the used data sets (e.g., GPS, CDR, surveys), the accuracy of prediction never reaches the coveted 100%. The reasons are manyfold: the lack of ground truth data, human beings' complex nature and behavior, and the difficulty to forecast visits to non-routinary areas and discoveries of new places [8].…”
mentioning
confidence: 99%
“…For instance, Smith et al [11] showed that the limits of predictability can be refined if we exclude from the possible next locations those that are far away from the user's current position. Teixeira et al [13] quantified the impact of context on predictability estimates, showing that context does not always increase predictability.…”
Section: Related Workmentioning
confidence: 99%
“…Although previous work [10] analyzed individual human mobility in terms of exploration and preferential returns, Song et al's work and subsequent studies derived from it [4,5,[11][12][13] studied the predictability of a person's mobility considering one's mobility as a single monolithic entity. In this paper, we propose to study predictability in terms of two components, and we argue that separately studying such components can reveal important insights into the predictability of one's mobility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations